CULTURE AND INTELLECTUAL PROPERTY DEVELOPMENT IN INDONESIA - Sardjono, Agus (UI Scholars Hub, 2012)
Essentially, viewed from the perspective of culture, IPR appears to be a highly embellished and colorful concept. That may be one of the reasons why the implementation of IPR protection in a plural society with diverse interests such as Indonesia invites debate and heated discussion so frequently. Given such circumstances, it would be naïve for anyone to hold on to their own perceptions on IPR without taking into account the existence of other views which are based on subjectivity. Speaking of IPR development, either from the legal, technological or from the economic aspect, IPR cannot be viewed from one single perspective. And this is exactly where the main issue arises. It is often difficult for sectors that are dealing with IPR to take an inclusive standpoint. It is in such context that the cultural study of IPR development becomes significant, both from the economic as well as from the technological point of view. IPR should not be taken out of its context, namely the society in which culture lives and develops.